Modification of Learning Strategy: Current Conditions of Independent Curriculum Adaptive Physical Education Learning at Tamanwinangun State Special School - Burhaein, Erick; Budi, Agus Setia (Journal of Physical and Outdoor Education, 2024)
The aim of this study is to evaluate the current situation of adaptive physical education learning using the Merdeka Curriculum. The research method used was qualitative with a phenomenological approach, involving a number of adaptive physical education (APE) teachers who were active at Tamanwinnagun Kebumen State Special School as respondents. Data collection instruments consist of documentation sheets, observations and unstructured interviews. The results of the research show that physical education teachers observe that the lack of implementation can provide input to improve the implementation of adapted adaptive physical education learning in special schools, so that the obstacles faced can be overcome effectively. Data analysis is presented in four dimensions, namely the dimensions of learning models, learning methods, learning media, and learning facilities and infrastructure. However, the use of observation rubrics in analyzing results is not yet fully standardized. In conclusion, adaptive physical education learning at the Tamanwinnagun Kebumen State SLB which uses the independent curriculum is carried out by considering the students' needs and situations.